Relasi Gender dalam Sistem Kekerabatan Matrilineal - Sile, Angelius Chrisantho; Suwena, I Wayan; Arjani, Ni Luh (Humanis; Vol 24 No 2 (2020), 2020)
Doka Nikisi’e is a village located in Ngada district which adheres to the matrilineal kinship system. However, even though women holding rights in traditional houses, men also have important roles in the kinship system in the village of Nikisi'e. Therefore, to avoid discrepancy and insurgency, it’s necessary to have a good gender relation in both case. For DokaNikisi’e people, even though the matrilineal kinship system greatly glorifies women, they still consider that this’s not to give women an absolute power, but solely for the sake of harmony between both side.The matrilineal kinship system in DokaNikisi'e can be studied by applyingRatnaMegawangi’s nurture and nature theory, called role theory. Robert Linton. While the concepts used as a reference in this study are concept of gender, kinship system concept and matrilineal concept. This research is a qualitative research which is obtained by ethnographic research models. Data collection techniques used in this research are observation, interviews, literature studies, and data analysis that is useful for processing objects in the research location.The results of this research shows that there is a process in the matrilineal kinship system inDokaNikisi’e village which explains the stages of the matrilineal kinship is formed through the marriage system. And in this process explained the classification of roles between men and women and allotment of inheritance in traditional houses.Besides explaining the process, this research also explains the significations contained in the matrilineal kinship system in DokaNikisi’e village.